Ethical considerations for an imminent irruption of neurotechnologies in the public sphere - Pizarro Contreras, Roberto Plácido (Revista Ethika+, 2020)
This article aims to collect a series of considerations in the field of neurosciences that could conflict with the Habermas’ procedural ethics of discourse in the context of its realization of his deliberative democracy. They are related mainly to the influence and inevitability of cognitive biases and emotions in the breakdown of dialogue. This will serve the purpose of introducing the question of to what extent it is legitimate to intervene the functioning of the mind and with this that of the communicative rationalities of citizens through procedures and devices that institutionalize communication. The question acquires special relevance today, when there are already companies that, encouraged by the advances achieved by neurotechnologies, aspire to the design of brain-computer interfaces that suppress orality between deliberative agents and solve their discrepancies beforehand through robotic processes that put in questioning the continuity of personal autonomy and democratic deliberation and rationality as we know them.